Headmaster-teacher relationship in leading school - Gyimah, Godfred (2013)
The study explored principal-teacher relationships in four Junior High schools in the Sekyere South District of Ashanti in Ghana. One of the things that government, policy-makers and educators in Ghana rarely or never discuss is the value and significance of human connections - the relationships in schools. The focus of the study was to uncover the significance of developing and sustaining a high-quality relationship between principals and teachers for effective leadership and performance. Again, the study projects a broader conception of leadership, one that shifts away from the traditional thinking approach where the figure-head is seen as ultimately responsible for the school outcomes, to involve all staff members as a collective responsibility pro-cess. The qualitative case study adopted semi-structured one-to-one interviews to collect data from one principal and a teacher from each of the four schools selected. The data was analyzed through a content analysis approach. The results revealed that a quality exchange relationship between principals and teachers has a significant influence on cooperation, commitment and performance to both principals and teachers. The results also showed that working together in a cordial relationship and in a more democratic environment brings long-lasting dividend for the school and the learners. But these vital elements are mostly hampered by the mundane procedures, dictatorial decisions, strict supervision of the directorate of education and some principals. This had not only negatively affected the principals’ and teachers’ work roles and exchange relationship, but teaching and learning as well. These traditional behaviors have also created fear, pressure and resentment in teachers, and prevent them from sharing innovative ideas and being committed to school activities. The interpretation of this study was purely engrained in the respondents’ context. The study recommends a further study in a larger scale to ascertain the affect and effect of the results or the hypothesis revealed. Perhaps it might be good if further discussion can be done on enhancing a quality exchange relationship among principals, teachers, circuit supervisors and the directorate of education. Effective leadership occurs as a result of building a quality relationship with the leader and the led.